A91 T CELL-SPECIFIC DELETION OF NOD2 DOES NOT INFLUENCE MICROBIAL RESILIENCE FOLLOWING ANTIBIOTIC EXPOSURE OR MUCOSAL DAMAGE. (1st March 2018) - Marshall, K; Goethel, A; Croitoru, K
Abstract: Background: The cause of inflammatory bowel disease (IBD) involves interactions between host genetics, the environment and the gut microbiota. Environmental perturbations, such as antibiotics, induce transient shifts in the microbiota, which may alter T cell-mediated immune responses. We previously found that Nod2 knockout mice show a delayed microbial recovery following antibiotic treatment, and that this altered microbiota influenced the response to T-cell induced mucosal damage in the small intestine. Aims: We sought to determine if deletion of Nod2 specifically in CD4 + T cells would play a role in antibiotic induced dysbiosis and resilience of the microbiota and whether this could lead to an altered immune response. Methods: Adult Nod2 Flox and Nod2 ΔCD4 mice received either control or amoxicillin [200 mg/L] ad libitum for one week, followed by control water for four weeks. Stool samples were collected weekly to monitor changes in the gut microbial community. On day 35, small intestinal mucosal damage was induced by an intraperitoneal injection of 50μg anti-CD3. Results: On day 0, the gut microbiota of Nod2 Flox and Nod2 ΔCD4 littermates did not differ. Antibiotic treatment induced a reduction in the abundance of Firmicutes, including Lactobacillus and Clostridia, whereas Gamma-Proteobacteria and Bacteroidaceae increased compared to water-treated controls on day 7. Anti-CD3 injection induced mucosal damage resulting in increased levels of IFNγ and IL-17 in the small intestine, however there were no differences between genotypes or treatments. Myeloperoxidase, a measure of neutrophil activity, was significantly increased in Nod2 Flox mice as compared to Nod2 ΔCD4 littermates; however, this difference was ablated if the mice had previously received antibiotics. Conclusions: Our data indicates that while Nod2 is involved in microbial resilience and small intestinal mucosal damage, specific deletion of Nod2 in T cells does not recapitulate the phenotype. Together, this suggests that other (non-CD4 + T) cells are involved in the response to antibiotic-induced perturbations of the gut microbiota. Furthermore, altered microbial composition can influence neutrophil activity during mucosal damage in the small intestine. Funding Agencies: Department of Immunology, University of Toronto